Behind the Eight Ball: The Effects of Race and Number of Infractions on the Severity of Exclusionary Discipline Sanctions Issued in Secondary School. (September 2020) - Blake, Jamilia J.; Smith, Danielle M.; Unni, Asha; Marchbanks, Miner P.; Wood, Steve; Eason, John M.
African American and Hispanic students receive more punitive school discipline than White students even when students of color commit similar infractions as Whites. Similarly, students with a disability status are more likely to experience harsher discipline in schools compared to their counterparts without a disability label. This study examines whether these discrepancies are a result of a difference in the number of infractions students of different racial/ethnic groups and disability categories commit. Using secondary educational data from a state educational agency in the United States, we demonstrate that African American and Hispanic students and students with an emotional behavioral disorder status receive more severe sanctions than White students and students without a disability label at their first discipline encounter. This racial disparity in discipline severity continues through six sanctions and is eliminated at the 13th sanction. The disability disparity in discipline severity dissipates after 10 sanctions for students with emotional behavioral disorder and intellectual disability. Implications for school personnel and future directions are discussed.